واقع إستخدام الأساليب الكمية ونظم المعلومات في المؤسسة الإقتصادية - بارودة صافية, بن يزة فاطيمة (My University, 2022)
Technological developments and the information revolution have brought about significant changes in the workplace and decision-making process within institutions in order to keep pace with the international environment, and considering that the administrative decision-maker is the essence of the administrative process The latter is done only through the organizations' ability to adopt quantitative technologies and effective information systems, This study was aimed at demonstrating the importance of using quantitative methods and information systems and the reality of using them in the Association of Peasant Cooperatives (UFCP) Foundation with a view to achieving the study's objectives above. and the Social Science Statistical Package Programme (SPSS) was used to analyse the form's data. We have concluded several findings, most notably that the Foundation has an effective information system that provides the necessary information accurately and reliably and that the reality of its use of quantitative methods is medium, i.e. it needs to use quantitative methods more because of its importance and broad role in improving the decision-making process
دراسة حالة مؤسسة التعاونية القلاحية مستغانم
Keywords: words: Information Systems، Quantitative Methods، Management Decision، economic foundation ،operations research